2-{[Bis(propan-2-yl)carbamothioyl]sulfanyl}acetic acid - Lee, See Mun *; Ainnul H. S. Azizan, *; Lo, Kong Mun *; Tan, Sang Loon *; Tiekink, Edward R. T. * (MDPI, 2019)
The title compound, (iPr)2NC(=S)SCH2C(=O)OH (1), was synthesized by conventional methods and its X-ray crystal structure was determined by X-ray crystallography. The compound was further characterized by analytical, IR, UV, 1D NMR (1H and 13C{1H}), and 2D NMR (DEPT135) spectroscopy, and density functional theory (DFT) methods. X-ray crystallography on 1 confirms the formulation and reveals a nearly orthogonal relationship between the planar NCS2 and C2O2 residues. In the crystal, hydroxyl-O–H⋯O(carbonyl) hydrogen bonds lead dimers via an eightmembered {⋯OCOH}2 ring.